A fixed-point approach for azimuthal equatorial ocean flows. Issue 1 (2nd January 2022) - Iulian Martin, Calin; Petruşel, Adrian
Abstract : We present a study of equatorial ocean flows exhibiting geophysical effects, a complex vertical structure and moving in the azimuthal direction, with no variation in this direction. By means of a fixed-point approach, we study the relation between the pressure at the free surface of such flows and the resulting distortion of that free surface. The method in the present paper allows us to enlarge the class of nonlinearities from our previous works.